Penambahan Suplemen Madu dalam Pakan Guna Meningkatkan Pertumbuhan Dan Kelulushidupan Benih Lobster Air Tawar Red Claw (Cherax quadricarinatus) [The Addition Supplement Of Honey In Feed To Increasing Growth And Survival Rate Of Freshwater Crayfish Seed Red Claw (Cherax quadricarinatus) ] - Akhmad Taufiq Mukti; Fachriza Tri Aprilia; Jola Rahmahani; Muhammad Arief (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
Abstract The demand for domestic or worldwide market to freshwater crayfish is high. Wherefor, needed some cultivation to reach that demand. The growth period of freshwater crayfish is slowly, then to increase growth needed addition some supplement in the feed. The aim of this research was to find out the influence of addition honey in the feed concerning to growth and survival rate freshwater crayfish seed red claw (C. quadricarinatus) and also to figure out the best dose of addition honey which one could increase growth and survival rate of freshwater crayfish red claw (C. quadricarinatus) seed. The method in the research was used Completely Randomized Design with 9 treatment. The addition doze of honey in every feed is different such as A (0 ml/kg of feed) as control, B (300 ml/kg of feed), C (400 ml/kg of woof), D (500 ml/kg of feed), E (600 ml/kg of feed), F (700 ml/kg of feed), G (800 ml/kg of feed), H (900 ml/kg of feed) dan I (1000 ml/kg of feed), in every treatment must repeated 3 times. The result of this research figure out that an addition honey in feed of freshwater crayfish red claw (C. quadricarinatus) was not obviously influence to growth and also survival rate. The best doze of honey to add in feed of freshwater crayfish red claw (C. quadricarinatus) to reach maximal weight growing up is 800 ml/kg of feed.